Pengaruh Kampanye 'Isi Piringku' terhadap Tingkat Pengetahuan Gizi Seimbang Siswa SDT Excellent Mandiri School Kota Jambi - Sofiyetti Sofiyetti; Dona Muin; Elen Yusmi Elita (NHM PRESS, 2023)
Throughout the life cycle, nutrition is central to health and well-being. Nutrition education is important for school children because they can determine the food and drink choices they want. This nutritional knowledge influences consumption patterns so that it is hoped that school children will have good nutritional status so that their growth and development and activities will run well. This research aims to determine the effect of balanced nutrition education through the fill my plate campaign on the level of knowledge of students about balanced nutrition at SDT Excellent Mandiri School, Jambi City. This research method uses the Quasi-Experiment method with the Non-Randomized Without Control Group Pretest and Posttest Design approach. The sample for this study consisted of 60 respondents who met the inclusion and exclusion criteria. Research results: All 60 respondents (100%) experienced an increase in their scores during the posttest from their previous pretest scores. Of the 60 respondents, the average score obtained before the balanced nutrition education with the fill my plate campaign was 5.23 with a minimum score of 2 and a maximum score of 8, while the average score after the health education (post-test) was 8.43 with a minimum score of 7 and maximum score is 10. This shows an increase in the pre-test score with the average comparison score between the pre-test and post-test being 3.2. The results of the bivariate analysis test with the Wilcoxon T-Test on Pre-test and Post-Test respondents. The results of data testing showed a p value = 0.000, so it can be concluded statistically that there is a significant difference in knowledge between knowledge before and after the balanced nutrition education intervention with the Fill My Plate campaign. Statistically there is a significant difference in knowledge between knowledge before and after the balanced nutrition education intervention with the fill my plate campaign. For schools, because there is no food provision from the school, it is hoped that the school will monitor the food menu sold in the canteen and what children consume during class breaks. Students are advised to bring healthy supplies from home that meet a balanced nutritional pattern.